VD_FINDINFO HC / 2015 / 892 vom 27. Oktober 2015 - VD Tribunal cantonal (2015)
DÉCISION D'IRRECEVABILITÉ, DÉLAI DE RECOURS, EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE | 321 al. 2 CPC (CH), 321 CPC (CH), 337 CPC (CH), 339 al. 2 CPC (CH)